Análise teórica e experimental do comportamento de grandes e pequenos sinais e desenvolvimento de um novo modelo dinâmico de pequenos sinais do conversor ZVS-PSM-FB. - Zanatta, Cleber (2006)
This Master Thesis presents the development of a new dynamic model for the DC-DC Zero-Voltage-Switching Phase-Shift-Modulated Full-Bridge (ZVS-PSM-FB).At first, the ZVSPSM-FB converter is analyzed and the Steady-State equations are derived. Then, using the ac equivalent circuit modeling technique, it is derived two new ZVS-PSM-FB dynamical models, based on step operation of the converter and steady-state converter equations. These two new ZVS-PSM-FB dynamical models with two dynamical models previously presented in the literature are used to perform a frequency response and a transfer-function DC-gain comparison to verify the performance of the dynamical models. Comparison results shows that our second model here derived presents a better performance among other models, keeping the desirable characteristics as simple polynomial ratio transfer-functions, excellent theoretical accuracy of transfer-functions DC-gains, transfer-functions coefficients independency of circuit parasitics components, excepting the primary leakage inductance. Even in this work, it is shown frequency response experimental results of the ZVS-PSM-FB converter, designed following telecommunications rectifiers power supplies standards.